Sinergi ESG dan Komite Audit: Strategi Menuju Kinerja Keuangan yang Berkelanjutan - Putri Elwira, Mutia Nurullita; Dwita, Sany; Hayati, Dian Indah; Raga, Ridha Azka (Wahana Riset Akuntansi, 2025)
Purpose – This study aims to examine the influence of ESG performance and the audit committee on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) during 2021-2023.Design/methodology/approach – The sample in this study consisted of 72 companies listed on the Indonesia Stock Exchange, with a total of 216 observations. The data analysis method used was multiple linear regression analysis with SPSS 25.Findings – The results of the hypothesis test for partial effects (t-test) indicate that ESG performance has a positive and significant effect on financial performance. Meanwhile, the audit committee variable has a negative and significant effect on financial performance.Originality/value – This study is novel in that it examines the influence of Environmental, Social, and Governance (ESG) performance and Audit Committees on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The research's novelty lies in the post-pandemic observation period, which represents the economic recovery phase, and in examining the interaction between ESG performance and Audit Committee effectiveness in improving financial performance.Research limitations/implications – This study contributes by simultaneously examining the role of ESG performance and the audit committee in influencing financial performance. While prior research has largely focused on these aspects separately, this study integrates sustainability performance and corporate governance mechanisms, offering a more comprehensive perspective. The findings provide both theoretical enrichment and practical implications, showing that strong ESG practices supported by an effective audit committee can enhance financial outcomes and long-term firm value.Keywords: ESG performance, audit committee, corporate governance, financial performance, emerging economyArticle Type: Research Paper.